Comparative Analysis of Portfolio Performance Between Value Stocks and Growth Stocks During the Covid-19 Pandemic - Huda, Aulia Nurul; Kurniana; Raharjo, Taufik (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2024)
This research aims to analyze the performance of value-stock and growth-stock portfolio during the pandemic to learn which investment strategy gave better performance during the period. This research is conducted using t-test to compare the average weekly return between value-stock and growth-stock portfolio. The performance of value stock portfolio is represented by IDX Value 30 index performance, while growth stock portfolio is represented by IDX Growth 30 index performance. This research shows that there is no significant difference between the performance of value-stock and growth stock portfolio during the pandemic. Later, this research also uses risk-adjusted return in the return to include risk in return calculation. However, the result remains the same as there is no significant difference between these two portfolios. Therefore, we can conclude that the two investment strategies did not give different results significantly during the pandemic.